Vertical vein aneurysm in supracardiac total anomalous pulmonary venous connection - Niraj Nirmal Pandey; Arun Sharma; Sanjeev Kumar (Wolters Kluwer Medknow Publications, 2019)
Aneurysmal dilatation of the vertical vein in a case of supracardiac total anomalous pulmonary venous connection (TAPVC) is an extremely rare condition. It has been reported to occur secondary to severe compression of the vertical vein when it traverses between the left bronchus and the left pulmonary artery. We present a 14-year-old male with supracardiac TAPVC with a vertical vein aneurysm, probably secondary to stenosis caused by a thin membranous web just proximal to the aneurysm.